Intentional Semantics for Molecular Biology - Haeusler, Edward H.; Cuconato, Bruno; Glatzl, Luiz A.; Guateque, Maria L.; Vieira, Diogo M.; de Armas, Elvismary M.; Baião, Fernanda; Catanho, Marcos; de Miranda, Antonio B.; Lifschitz, Sergio (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2023: Anais do XVI Simpósio Brasileiro de Bioinformática, 2023)
This article presents an intentional semantics, using Object Petri Nets (OPNs), to assign activity to each biological molecule and complex, such as mRNA, tRNA, ribosomes, and protein synthesis. The work differs from traditional uses of Petri Nets in Biology and Chemistry for being a bottom-up and general semantics and not only a formalization of some molecular biological phenomenon. Assigning activities to every molecule and the difference between biological function and activity is also a conceptual contribution of this work. To illustrate our semantics, we set to tRNA, mRNA, ribosome, and the protein transcription molecular complex the respective activities expressed by OPNs.